The straight line : from soldier king to soldier dictator - Herz, Carl; Dukes, Chas.; Fitzgerald, Edward (London : Hutchinson, 1942)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: nationalisme; militarisme; Pruisen; Duitsland